Catastrophizing is associated with pain-related disability in temporomandibular disorders - Cintia Regina Andrade SOUSA; Ynara Bosco de Oliveira Lima ARSATI; Ana Miriam VELLY; Carlos Alberto Lima da SILVA; Franco ARSATI (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This study aimed to evaluate the association of pain-related disability with biopsychosocial factors in temporomandibular disorders (TMD) patients. The study was carried out at the Orofacial Pain Outpatient Clinic of the State University of Feira de Santana, Bahia, from September 2018 to March 2020. The sociodemographic aspects, TMD subtypes, presence of pain-induced disability, pressure pain threshold, perceived stress, anxiety, depression, and catastrophizing were evaluated in 61 patients. The studied variables were compared between patients with and without pain-induced disability. Crude and adjusted logistic regression were performed to obtain estimates of odds ratios (OR) and 95% confidence intervals. With the exception of catastrophizing, there was no association between the biopsychosocial factors and pain-induced disability. The presence of catastrophizing increased the chance of having chronic pain-induced disability by 4.02 times. The results of this study indicate a strong association between pain catastrophizing and disability in individuals with chronic painful TMD.